KEBIJAKAN PEMERINTAH DAERAH TENTANG KAWASAN TANPA ROKOK DALAM PENINGKATAN KESEHATAN MASYARAKAT - Santosa S.H., M.H. (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2013)
Health is a human right. Healthcare efforts performed integrated and sustainable to maintain and improve public health degree in the form of disease prevention. But the intended effort is going hampered by the fact that most residents have smoking habit that affects health, either to the concerned person and the surrounding areas. The cigarette industry has provided very large economic and social benefits, also the greater income tax. Farmers make tobacco leaves as their foundation of life. Report of the Basic Health Research result of 2010 stated that nationwide smoking prevalence reached 34.7%. It means that more than one third of Indonesian people are smokers. The Ministry of Health estimated in 2020 that the disease is related to smoking will cause the deaths of 8.4 million people per year. Security of addictive substances tobacco products which performed by the government and local governments is through realize no-smoking area.